Enhancing Student Engagement in Elementary Science and Social Studies Through the Contextual Teaching and Learning Approach: Evidence from a Quasi-Experimental Study - Afifa Tsabita Muttaqya; Suswandari (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
Student engagement is one of the key factors contributing to successful learning. However, student engagement in Science and Social Studies (IPAS) continues to face several challenges, resulting in learning outcomes that have not yet reached the expected objectives. One effort to address this issue is the implementation of a student-centered instructional approach. This study aimed to examine the effectiveness of the Contextual Teaching and Learning (CTL) approach in improving student engagement. This study employed a quantitative method using a quasi-experimental design with a Nonequivalent Control Group Design. The participants consisted of 54 fifth-grade students at SDN Srengseng Sawah 15, including 28 students in the experimental group and 26 students in the control group. Data were analyzed using the N-Gain, Shapiro–Wilk normality, and Mann–Whitney U tests. The results showed a Mann–Whitney U significance value of 0.000 (p < 0.05), indicating a significant difference in student engagement between the experimental and control groups, with a large effect size (r = 0.67). The experimental group achieved a mean N-Gain score of 0.769 (high) with an effectiveness level of 76.92%, whereas the control group obtained a mean N-Gain score of 0.460 (moderate) with an effectiveness level of 45.99%. These findings indicate that the Contextual Teaching and Learning (CTL) approach is effective in improving student engagement in Science and Social Studies (IPAS).